A General Route to Prepare Low‐Ruthenium‐Content Bimetallic Electrocatalysts for pH‐Universal Hydrogen Evolution Reaction by Using Carbon Quantum Dots - Liu, Yuan; Li, Xue; Zhang, Qinghua; Li, Weidong; Xie, Yu; Liu, Hanyu; Shang, Lu; Liu, Zhongyi; Chen, Zhimin; Gu, Lin; Tang, Zhiyong; Zhang, Tierui; et al. (Angewandte Chemie International Edition, 2020)
A challenging but pressing task to design and synthesize novel, efficient, and robust pH‐universal hydrogen evolution reaction (HER) electrocatalysts for scalable and sustainable hydrogen production through electrochemical water splitting. Herein, we report a facile method to prepare an efficient and robust Ru‐M (M=Ni, Mn, Cu) bimetal nanoparticle and carbon quantum dot hybrid (RuM/CQDs) for pH‐universal HER. The RuNi/CQDs catalysts exhibit outstanding HER performance at all pH levels. The unexpected low overpotentials of 13, 58, and 18 mV shown by RuNi/CQDs allow a current density of 10 mA cm−2 in 1 m KOH, 0.5 m H2SO4, and 1 m PBS, respectively, for Ru loading at 5.93 μgRu cm−2. This performance is among the best catalytic activities reported for any platinum‐free electrocatalyst. Theoretical studies reveal that Ni doping results in a moderate weakening of the hydrogen bonding energy of nearby surface Ru atoms, which plays a critical role in improving the HER activity. How low can Ru go: A scalable and general synthetic method for the preparation of transition‐metal‐doped RuM/carbon quantum dots (CQDs; M=Ni, Mn, Cu) has been developed through metal‐mediated CQD condensation and carbonization. The low‐ruthenium‐content RuM/CQD catalysts exhibit outstanding activity and stability in catalyzing hydrogen evolution at all pH values.